Promotion of lateral growth of GaN crystals on point seeds by extraction of substrates from melt in the Na-flux method. (27th March 2019) - Imanishi, Masayuki; Murakami, Kosuke; Yamada, Takumi; Kakinouchi, Keisuke; Nakamura, Kosuke; Kitamura, Tomoko; Okumura, Kanako; Yoshimura, Masashi; Mori, Yusuke
Abstract: In a previous study, we successfully obtained large-diameter, low-dislocation-density GaN wafer using the Na-flux multi-point seed (MPS) technique. However, the lattice constants of the GaN wafer grown by this technique expanded due to oxygen concentration in pyramidal facets. We here invented a breakthrough technique for the promotion of lateral growth, and succeed in suppressing pyramidal facet growth by residual flux formed after extraction of the MPS-GaN substrate from the Na-Ga melt in a crucible. The surface of the grown wafer was fully composed of the c -plane and showed low oxygen concentration, so expansion of lattice constants could be successfully prevented.